LEGAL ANTHROPOLOGY: THEORETICAL STUDIES, SCOPE, AND DEVELOPMENT FROM A CULTURAL AND SOCIAL NORM PERSPECTIVE - Yoga, Rizky (Hukum tata Negara/Siyasah, 2025)
This article was written with the aim of imparting knowledge to readers and making it easier for those who have difficulty finding literature, representatives to facilitate the learning process, and therefore the learning objectives are well achieved. This article uses the literature review method by analyzing various information that is considered related to the discussion and problems that are the object of study. The results analyzed explain that through legal anthropology, material in the form of understanding, scope, and legal anthropology approaches that can be found and related to social institutions can be studied to advance knowledge about Islamic legal anthropology in the entire country community.Keywords: Anthropology of Islamic Law